(untitled) (Research, Society and Development, 2025)
This study presents a learning model for teaching aeromedical care based on a methodological approach with a comprehensive review of the literature and development of educational technology, creating an optional course on aeromedical care and an e-book as a teaching support instrument focusing on pedagogical practice involved in this process. Its objective is to develop an educational technology in the format of a didactic sequence on Aeromedical Nursing care in undergraduate nursing courses. This is a methodological development study, with an integrative review of the literature. An optional 30-hour course was prepared, which still needs to be validated with a competency matrix on aeromedical care based on Ordinance MS-GM 2,048 of November 5, 2002, which deals with the National Emergency Care Policy and COFEN Resolution 656 /2020 that regulates the role of nurses in direct assistance and management of Mobile Pre-Hospital Care and Inter-Hospital in air vehicle. RIL pointed to the need to create an educational technology for aeromedical teaching considering that an instrument aimed at nursing undergraduates was not identified in the literature. It is worth noting that the methodology as a whole favored the construction of the meaning of learning and critical reflection as the basis for transformation. It is concluded that the creation of an optional subject and the elaboration of an e-book on aeromedical nursing care.